Avaliação da atividade antinociceptiva espinal da toxina Ph1 isolada dp veneno da Phoneutria nigriventer em rodedores - Alessandra Hubner de Souza (2008)
Calcium influx through voltage sensitive calcium channels (VSCCs) plays an important role on the nociceptive transmission in the dorsal horn of the spinal cord. The intrathecal administration of VSCCs blockers, such as -conotoxin-MVIIA (-CTx-MVIIA) has analgesic effect, but it narrows the therapeutic window, presenting many adverse effects. The Brazilian spider Phoneutria nigriventer venom contains a variety of substances with predominantly neurotoxic action, among them the Ph1 which was recently described as a potent neurotransmission blocker for interacting with N-type voltage sensitive calcium channels. In this study, we verify the analgesic potential of Ph1 by its intrathecal administration in acute and persistent pain models in rodents. The Ph1 produced a prolonged antinociception and with great effectiveness in the hot plate model in mice when compared to -CTx-MVIIA. However, Ph1 or -CTx-MVIIA did not produce adverse motor effects in mice. Ph1 was more effective and powerful than -CTx-MVIIA when assessed in rats, not only in preventing the nociception induced by formalin, but particularly in reversing the persistent inflammatory nociception previously installed. Furthermore, the analgesic action of both toxins was related to inhibition of pro-nociceptive neurotransmitter release evoked by calcium in the spinal cord, such as glutamate. When the adverse effects were evaluated in rats, we verified that Ph1 had a therapeutic index higher than -CTx-MVIIA. However, both toxins were able to produce blood pressure alterations. In addition, the treatment with Ph1 toxin is able to reduce the acute nociception induced by surgical incision, or chronic, caused by arthritis or by sciatic nerve injury in rodents. Finally, the recombinant Ph1 toxin xvi expressed in Escherichia coli showed an antinociceptive activity similar to native toxin. Thus, the present study demonstrated that Ph1 toxin presented analgesic effects in different models of pain, suggesting that this toxin may have a potential to be used as a drug for the control of the persistent pain.